Numerical solution of Kolmogorov equation using compact - Pooyandeh, Sara; Radpoor, Marzieh Karimi (IJRDO -JOURNAL OF MATHEMATICS, 2016)
In this study, we solve the Kolmogorov equation by a compact finite difference method.We apply a compact finite difference approximation for discretizing spatial derivatives.Then, using cubic C1-spline collocation technique, we solve the time integration of theresulting system of ordinary differential equations. This joined method has fourth-orderaccuracy in both space and time variables, that is this method is of order O(h4, k4). Thenumerical results confirm the validity of this method